Wireless Body Area Networks Routing Protocols: A Review - Khalid Awan; Kashif Naseer Qureshi; Mehwish Mehwish (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Wireless Body Area Networks (WBANs) are designed for monitoring the patient’s conditions and assist them in critical health situation. Tiny size wireless sensors sense the data related to patient health. Further, the sensed data sends to base station for further process. The base station sends the data to the nearest sink node or to the nearest medical center or hospital. In order to complete this entire process, wireless sensors need efficient routing without any error or delay. The routing protocols have been suffered with various challenges and issues which are related to the routing and energy issues. This paper provides a comprehensive survey of important existing routing protocols for WBANs. Paper also discusses the protocols strengths, limitations with their critical analysis.